Perivascular Unit: This Must Be the Place. The Anatomical Crossroad Between the Immune, Vascular and Nervous System - Troili, Fernanda; Cipollini, Virginia; Moci, Marco; Morena, Emanuele; Palotai, Miklos; Rinaldi, Virginia; Romano, Carmela; Ristori, Giovanni; Giubilei, Franco; Salvetti, Marco; Orzi, Francesco; Guttmann, Charles R. G.; et al. (Frontiers in Neuroanatomy, 2020)
Most neurological disorders seemingly have heterogenous pathogenesis, with overlapping contribution of neuronal, immune and vascular mechanisms of brain damage. The perivascular space (PVS) in the brain represents a crossroad where those mechanisms interact, as well as a key anatomical component of the recently discovered glymphatic pathway, which is considered to play a crucial role in the clearance of brain waste linked to neurodegenerative diseases. The pathological interplay between neuronal, immune and vascular factors can create an environment that promotes self-perpetration of mechanisms of brain damage across different neurological diseases, including those that are primarily thought of as neurodegenerative, neuroinflammatory or cerebrovascular. PVS changes can be monitored in humans in vivo using magnetic resonance imaging (MRI). In the context of glymphatic clearance, MRI-visible enlarged perivascular spaces (EPVS) are considered to reflect glymphatic stasis secondary to the perivascular accumulation of brain debris, although they may also represent an adaptive mechanism of the glymphatic system to clear them. EPVS are also established correlates of dementia and cerebral small vessel disease (SVD) and are considered to reflect brain inflammatory activity. In this review, we describe the “perivascular unit” as a key anatomical substrate for the interaction between neuronal, immune and vascular mechanisms of brain damage, which are shared across different neurological diseases, including those that are considered primarily neurodegenerative, neuroinflammatory or cerebrovascular. We will describe the main anatomical, physiological and pathological features of the perivascular unit, highlight potential substrates for the interplay between different noxae and summarize MRI studies of EPVS in cerebrovascular, neuroinflammatory and neurodegenerative disorders.